O Programa Novo Mais Educação na escola M.E.I.F. Pedro Coelho da Mota em Castanhal: desenvolvimento, dificuldades e contribuições - SILVA, Fernanda Alves (2019)
This Work of conclusion of course (CBT) titled "the new program More education in M.E.I.F. school Pedro Coelho da Mota in Castanhal/PA: development, problems and Contributions" is the result of a field research carried out in a municipal school a peripheral district of the urban area of the city of Castanhal/PA. Analyses the implementation of the program at school, understanding your implementation, difficulties and contributions to school education, from a context where the target education policy is the full-time education in Brazil. The study is based on a qualitative research approach, based methodologically on a case study. Data collection and information was given from the structured interview which was conducted with the following agents of the program at school: articulator, mediators and facilitators. The data were organized and analyzed based on the ideas of authors who argue the integral education and full-time, such as: Cavaliere (2007), New Delhi (2006), Ribeiro (2017), Moll (2012), among others. From this work it was possible to observe that the implementation of the program on the school from the need to improve the performance of students, as well as develop their multiple human dimensions, from the perspective of full time education integral is targeted by the new program More education. During the process, some difficulties were present, among them, the low frequency of students in the program and the lack of teaching material to carry out the activities. Despite these impasses, the program had good results with respect to the performance of the performance of the students participating in the program.